2007
DOI: 10.1016/j.yebeh.2007.08.007
|View full text |Cite
|
Sign up to set email alerts
|

MRI volume loss of subcortical structures in unilateral temporal lobe epilepsy

Abstract: Few studies have examined the relative degree of brain volume loss in both the hippocampi and subcortical structures in unilateral temporal lobe epilepsy (TLE), and their association with clinical seizure correlates. In this study, quantitative MRI volumes were measured in the hippocampus, thalamus, caudate, putamen, and corpus callosum in 48 unilateral TLE patients (26 rights, and 22 lefts) and compared to 29 healthy controls. The ipsilateral hippocampus, corpus callosum, and bilateral thalami showed the grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 40 publications
3
38
0
4
Order By: Relevance
“…41 This caveat appears particularly relevant for cross-sectional studies. In 18 of the latter (47.4%), 14,16,[20][21][22]24,30,[33][34][35][36][37][38]40,42,[50][51][52] no statistical approaches were implemented to correct for the effects of age. Although the remaining studies addressed aging, no consistent method was chosen: 3 reported no significant effects of age on morphometric measures in controls, 15,32,48 3 found no effect of age or no effect of age at epilepsy onset in patients, 19,29,53 2 corrected for age at onset, 18,28 5 corrected for age in patients, 17,26,47,49,54 4 utilized MRI measures adjusted for age 13,31,39,46 (based on regression models derived from controls), 1 calculated epilepsy duration/age ratios, 23 2 statistically compared chronological age effects between patients and controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 This caveat appears particularly relevant for cross-sectional studies. In 18 of the latter (47.4%), 14,16,[20][21][22]24,30,[33][34][35][36][37][38]40,42,[50][51][52] no statistical approaches were implemented to correct for the effects of age. Although the remaining studies addressed aging, no consistent method was chosen: 3 reported no significant effects of age on morphometric measures in controls, 15,32,48 3 found no effect of age or no effect of age at epilepsy onset in patients, 19,29,53 2 corrected for age at onset, 18,28 5 corrected for age in patients, 17,26,47,49,54 4 utilized MRI measures adjusted for age 13,31,39,46 (based on regression models derived from controls), 1 calculated epilepsy duration/age ratios, 23 2 statistically compared chronological age effects between patients and controls.…”
Section: Resultsmentioning
confidence: 99%
“…Hippocampal measures were frequently based on manual volumetry (n 5 15, with 5 explicitly mentioning blinded assessment 14,16,17,24,50 ). Four more recent analyses 31,34,40,46 used automated approaches. Mixed-effect models revealed a significant moderator effect of volumetric technique (automated vs manual) for results reported on the ipsilateral hippocampus, both for correlational analyses with epilepsy duration (p 5 0.02; amount of variance accounted for: 46.55%, I…”
Section: Resultsmentioning
confidence: 99%
“…Smaller volumes of the striatum and pallidum were described in various idiopathic generalized epilepsy syndromes. The loss of putamen volume was bilaterally associated with absent or rare generalized tonic-clonic seizures, implicating the putamen in the control of the most disabling seizure type, independent of the site of neocortical focus [20,21]. The antiepileptic effects of neurostimulation of the intralaminar thalamic nuclei, specifically of the centromedian and parafascicular nuclei in generalized seizures and in Lennox-Gastaut syndrome [22], may be also mediated by regulating BG activity via the thalamo-striatal projections [23].…”
Section: The Bg In Generalized and Extratemporal Epilepsiesmentioning
confidence: 98%
“…[1][2][3] Although most MR imaging studies focus on the limbic structures, changes in the extrahippocampal and extratemporal areas have also been observed in patients with mesial TLE. [4][5][6] However, although the main neuropathologic substrate of hippocampal atrophy has been identified as neuron loss, [7][8][9] the substrate of extrahippocampal and extratemporal atrophy is not fully understood. Because conventional MR imaging has limited specificity, the interpretation of GM and WM differences between patients with epilepsy and healthy controls may be problematic when subtle changes in brain structure are observed in association with neurologic and psychiatric diseases.…”
mentioning
confidence: 99%